Alterasi Akibat Proses Hidrothermal di Bolaang Mongondow, Provinsi Sulawesi Utara - Harjanto, Agus; Sutanto, Sutanto; Sutarto, Sutarto; Subandrio, Achmad; Suasa, I Made; Salamat, Juanito; Hartono, Gia; Saputra, Putu; Basten, I Gde; Fauzi, Muhammad; Rosdiana, Rosdiana (EKSPLORIUM, 2016)
Bolaang Mongondow is located in central north Sulawesi arm, which is composed of Neogen magmatic arc and potentially contain economic minerals. This condition is behind the research purpose to study the mineral resources potencies. Research aim is to study alteration caused by hydrothermal process and its relation with gold (Au) deposit based on field study and laboratory analysis. Methodologies used for the research are literature study, geological survey, rocks sampling, laboratory analysis, and data processing. Research area is a multiply diorite intrusion complex. Andesite, volcaniclastic rocks, and dacite, the older rocks, were intruded by this complex. Later, dacitic tuff, volcanic sandstone, and alluvium deposited above them. There are three measured and mapped major faults heading NE-SW crossed by E-W fault and NW-SE fault lately crossed all the older faults. Early stage hydrothermal alteration related to the existence of young quartz diorite, showing alteration stage from the potassic center to distal prophyllitic. Final stage hydrothermal alteration consist of argilic, advanced argilic, and silica-clay mineral±magnetite±chlorite alteration overlapping the earlier alteration. Mineralization of Cu-Au±Ag in central part of research area or Tayap-Kinomaligan area is mostly asociated with potassic altered young quartz diorite and crossed by paralel and stockworked quartz-magnetite-chalcopyrite±bornite vein.